2021
DOI: 10.3390/md19090489
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Marine Alkaloid 3,10-Dibromofascaplysin Induces Apoptosis and Synergizes with Cytarabine Resulting in Leukemia Cell Death

Abstract: Myeloid leukemia is a hematologic neoplasia characterized by a clonal proliferation of hematopoietic stem cell progenitors. Patient prognosis varies depending on the subtype of leukemia as well as eligibility for intensive treatment regimens and allogeneic stem cell transplantation. Although significant progress has been made in the therapy of patients including novel targeted treatment approaches, there is still an urgent need to optimize treatment outcome. The most common therapy is based on the use of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…3,10-Dibromofascaplysin (DBF) (a halogenated fascaplysin alkaloid) derived from Fascaplysinopsis reticulata . The effect of DBF on leukemia cells was tested by Spirin et al, and the results showed that after DBF treatment of myeloid leukemia cells, the expression of E2F1 is upregulated, leading to the blockage of the S and G2 phases’ cell cycle, which in turn may lead to apoptosis [ 152 ]. FMS-like tyrosine kinase 3 (FLT-3) and c-kit are type III receptor tyrosine kinases that play an important role in cell survival, proliferation, and apoptosis.…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
See 1 more Smart Citation
“…3,10-Dibromofascaplysin (DBF) (a halogenated fascaplysin alkaloid) derived from Fascaplysinopsis reticulata . The effect of DBF on leukemia cells was tested by Spirin et al, and the results showed that after DBF treatment of myeloid leukemia cells, the expression of E2F1 is upregulated, leading to the blockage of the S and G2 phases’ cell cycle, which in turn may lead to apoptosis [ 152 ]. FMS-like tyrosine kinase 3 (FLT-3) and c-kit are type III receptor tyrosine kinases that play an important role in cell survival, proliferation, and apoptosis.…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…When DBF was combined with the PARP inhibitor, olaparib, it had a synergistic inhibitory effect on cancer cells, which may be caused by the accumulation of ROS [ 322 ]. In addition, the combination of DBF, a strong inducer of apoptosis, and cytarabine can cause pronounced synergistic cytotoxic effects on different myeloid leukemia cells in vitro and finally inhibit the growth of leukemia cells [ 152 ]. As mentioned above, EE-84, as an aplysinopsin derivative, has potential antileukemic effects.…”
Section: Combination Therapies Of Indole Alkaloidsmentioning
confidence: 99%
“…Remarkably, 3,10-dibromofascaplysin was able to suppress the cell metabolism at non-cytotoxic concentrations [ 28 ]. Further studies to determine the mechanism of the antitumor activity conducted in myeloid leukemia cells revealed that 8 activates the transcription factor E2F1 and decreases the expression of several genes responsible for cancer cell survival [ 29 ]. In addition, in human prostate cancer cells, we identified JNK1/2 to be one of the primary molecular targets of 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 8 could synergize with PARP-inhibitor Olaparib, presumably due to the induction of ROS production and consequent oxidative DNA damage mediated by the drug [ 30 ]. Additionally, 8 increased the effects of well-established drugs such as cytarabine, cisplatin, carboplatin, as well as docetaxel and cabazitaxel [ 28 , 29 ]. Despite some promising results published in recent years, the cytotoxicity to normal (non-cancer) cells was assumed to be the main challenge for fascaplysin and related compounds on their way to clinically approved drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that this alkaloid can induce apoptosis and activate an E2F1 transcriptional factor. Additionally, a synergistic effect of 3,10-dibromofascaplysin in combination with cytarabine was reported [19]. A review article by Dyshlovoy represents an overview of the literature published within the last 8 years and is mainly devoted to marine cancerpreventive compounds [20].…”
mentioning
confidence: 99%